Reindeer trampling promotes vegetation changes in tundra heathlands: Results from a simulation experiment. (6th April 2020) - Egelkraut, Dagmar; Barthelemy, Hélène; Olofsson, Johan
Abstract: Question: Herbivores exert strong influences on vegetation through activities such as trampling, defoliation, and fertilization. The combined effect of these activities on plant performance may cause dramatic vegetation shifts. Because herbivore pressures and the relative importance of their different activities are not equally distributed across the landscape, it is important to understand their isolated effect. One example of an herbivore‐induced vegetation shift is the reindeer‐driven transition from a subarctic tundra vegetation dominated by dwarf shrubs into a more productive, graminoid‐dominated state. Here, we asked how each of the grazing activities by reindeer separately and combined shape vegetation composition. Location: Nordreisa, Norway. Methods: We used a field experiment over six summers to study the separate and interacting effects of reindeer trampling, defoliation, addition of faeces and removal of moss on tundra heath vegetation, and to identify which of these factors were most important in driving the plant community towards a graminoid‐dominated state. Results: The combination of all treatments resulted in the strongest changes in vegetation, but trampling was the single most important factor altering the vegetation composition by reducing the abundance of both evergreen and deciduous dwarf shrubs. In contrast to what was expected, none of our treatments, separate or combined, resulted in an increased abundance of graminoids in 5 years, although such rapid vegetation changes have been observed in the field in similar environmental conditions. Conclusions: Trampling is the key process by which reindeer influence the abundance of functional groups, but only many processes combined result in strong changes in community composition. Moreover, additional factors not included in this experiment, such as urine, may be important in causing a state shift to a graminoid‐dominated community. Abstract : Herbivores strongly affect vegetation composition. We know much about herbivore‐driven vegetation shifts, but much less about which herbivore activities, e.g. defoliation, trampling or addition of faeces, are crucial in driving them. This is important, because not all activities occur homogeneously in a landscape. We simulated the main activities of reindeer and show that trampling is an important driver of vegetation change.